A successful tale of sirolimus treatment in refractory vascular tumors - Iman Ahmed Ragab; Salwa Mostafa Abdel-Kader; Amr AbdelHamid AbouZeid; Shaimaa AbdelSattar Mohammad; Heba Gomaa Abdel Raheem; Nihal Hussien Aly (Elsevier, 2022)
Sirolimus use in vascular tumors is limited. We present two cases of refractory vascular tumors with impressive response to sirolimus, one with refractory kaposiform hemangioendothelioma with rapid reversal of thrombocytopenia and heart failure and the other with advanced beard distribution hemangioma with improvement of respiratory distress after prolonged respiratory support.